Percentile Degrees For Obesity Level and Body Composition In Secondary School Female students in Baghdad - Altay, Duaa; Altay, Usama (Journal of Physical Education, 2018)
Percentile Degrees For Obesity Level and Body Composition In Secondary School Female students in Baghdad The importance of the research lies in the importance of general health and obesity indicator in female secondary school students. The problem lies in the lack of obesity percentile studies and the level of fat in female secondary school students. The researchers aimed at finding percentiles as body mass and fat level indicator in secondary school students. The subjects were (4828) female secondary school students aged 13 – 15 years old. The researchers came up with percentile degree and recommended evaluating the percentile as body mass and fat level indicator in female students.